1998
DOI: 10.1103/physrevlett.81.4212
|View full text |Cite
|
Sign up to set email alerts
|

Do Interactions Increase or Reduce the Conductance of Disordered Electrons? It Depends!

Abstract: We investigate the influence of electron-electron interactions on the conductance of two-dimensional disordered spinless electrons. We present an efficient numerical method based on diagonalization in a truncated basis of Hartree-Fock states to determine with high accuracy the low-energy properties in the entire parameter space. We find that weak interactions increase the d.c. conductance in the strongly localized regime while they decrease the d.c. conductance for weak disorder. Strong interactions always dec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
81
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 28 publications
12
81
0
Order By: Relevance
“…However, at the extremes of the energy regime, the opposite appears to happen -the wavefunctions for the interacting system are more localized, at least in configuration space. (It has been shown [26] that EEI can, under certain conditions enhance either localization or delocalization, and this in fact has been found to be the case [10].) We discuss the enhanced localization at the band edges in the context of [26] [26], so the effect on localization depends on which is enhanced more.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, at the extremes of the energy regime, the opposite appears to happen -the wavefunctions for the interacting system are more localized, at least in configuration space. (It has been shown [26] that EEI can, under certain conditions enhance either localization or delocalization, and this in fact has been found to be the case [10].) We discuss the enhanced localization at the band edges in the context of [26] [26], so the effect on localization depends on which is enhanced more.…”
mentioning
confidence: 99%
“…In this model, W/t = e rnn /[r nn (1+ r nn )], so a small difference in r nn implies a comparatively larger one in W/t. This gives W/t ∼ 3, 5,10,20, 40, 90, 200, 500, 1000 for r nn = 4, 5,6,7,8,9,10,11,12, respectively. One must be careful, however, when comparing our results with those of other authors because here W/t = e C /t.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 This shows that the conductance of a disordered film depends on interplay between interaction and disorder. 21 We caution that since our experiments are limited to 1.8 K, we cannot rule out the possibility that a film which appears to be the last film on the insulating side, may, at lower temperature turn out to be superconducting. 15 .…”
mentioning
confidence: 99%
“…20 It has been shown that interactions may increase or decrease the conductance of a disordered 2D electron systemweak interactions increase the dc conductance in the localized regime while they decrease the conductance in the diffusive regime. 21 Strong interactions were always found to decrease the conductance. These considerations motivated our experiments.…”
mentioning
confidence: 99%